LOOKING FOR THE FORM OF INDONESIAN DEMOCRACY: STUDY OF PANCASILA IDEOLOGY TOWARDS CONCURRENT ELECTIONS IN 2024 - Osbin Samosir (Dinasti Publisher, 2021)
Indonesia’s democracy has taken huge leaps since the starting of reformation in 1998, compared to Soeharto’s authoritarian ruling (New Order) from 1966 to May 21, 1998, and during Soekarno’s ruling from the country’s independence in 1945 until 1966. One year after Soeharto’s fall on May 21, 1998, Indonesia held its first democratically election on June 7, 1999. The election was contested by 48 political parties. In 2004, Indonesia for the first time held its direct presidential election. One year later, Indonesia held its first regional elections, where voters directly elect governors, regents and mayors. The question is on whether the current democratic practices have been in accordance with all democratic values as intended by Pancasila ideology as the basic foundation for Indonesia in all political actions? Pancasila: 1). The belief in one God, 2). Just and civilized humanity, 3). Indonesian unity, 4. Democracy under the wise guidance of representative consultation, 5). Social justice for all peoples of Indonesia. The country’s founding fathers formulated the understanding of democracy based the traditional practices of democracy at the grassroots level which have lasted for centuries throughout the country. However what happens now is that Indonesia just imitated the posture of Western/European democracy. It turns out that Indonesian democracy is very fragile because it does not have a tradition of democracy that grows independently from Indonesia's fertile soil itself, but democracy is taken from other cultures that have grown and developed in Europe and then transplanted in Indonesian soil. Therefore, the format for direct elections in Indonesia must be reviewed for improvement.